No cases of asymptomatic SARS-CoV-2 infection among healthcare staff in a city under lockdown restrictions: lessons to inform 'Operation Moonshot'. (26th December 2020) - Martin, Christopher A; Jenkins, David R; Patel, Prashanth; Goss, Charles; Price, Arthur; Barton, Linda; Gupta, Pankaj; Zaccardi, Francesco; Brunskill, Nigel J; Haldar, Pranab; Khunti, Kamlesh; Pareek, Manish
ABSTRACT: Background: Leicester was the first city in the UK to have 'local lockdown' measures imposed in response to high community rates of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission. As part of this response, a directive was issued by NHS England to offer testing of asymptomatic healthcare workers (HCWs) at University Hospitals of Leicester NHS Trust (UHL) for SARS-CoV-2 infection. Methods: Between 20 July and 14 August 2020, we invited all HCWs at UHL to attend for SARS-CoV-2 testing by nucleic acid amplification (NAAT). We combined the result of this assay with demographic information from the electronic staff record. Results: A total of 1150 staff (~8% of the workforce) volunteered. The median age was 46 years (IQR 34–55), 972 (84.5%) were female; 234 (20.4%) were of South Asian and 58 (5.0%) of Black ethnicity; 564 (49.0%) were nurses/healthcare assistants. We found no cases of asymptomatic infection. In comparison, average community test positivity rate in Leicester city was 2.6%. Conclusions: Within the context of local lockdowns due to high community transmission rates, voluntary testing of asymptomatic staff has low uptake and low yield and thus its premise and cost-effectiveness should be re-considered.